The relevance of creating a new combination drug for the treatment of cognitive disorders - L. I. Kucherenko; V. H. Slobodianyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Cognitive impairment is one of the most pressing problems of modern medicine, as its prevalence is steadily increasing worldwide. This trend is due to several global factors, including population aging, urbanization, the spread of chronic diseases, as well as the impact of the COVID-19 pandemic. Stress and social factors play a special role in the growth of cognitive disorders, which in recent years have significantly increased their impact on the population. In Ukraine, the problem of cognitive disorders has become even more acute due to socio-economic challenges and the consequences of the military aggression of the Russian Federation. Constant stress, loss of loved ones, forced displacement and a general sense of danger significantly affect cognitive functions, such as memory, concentration and planning ability. Understanding the basic mechanisms of the development of cognitive disorders is key to developing effective therapeutic approaches. Current research demonstrates that key pathogenetic factors include neurodegeneration, vascular disorders, metabolic dysfunction, and the effects of chronic stress. This emphasizes the need to develop new combination drugs that could comprehensively affect several pathogenetic links.